The Urgency of Sustainability Disclosure in Indonesia’s Agricultural Regulations: A Legal Strategy for Achieving SDG 2 - Rusdiana, Shelvi; Situmeang, Ampuan; Winda Fitri (Nurani: jurnal kajian syari’ah dan masyarakat, 2025)
Agriculture has become one of the leading contributors to climate change, with rapidly increasing greenhouse gas emissions, despite its close connection to the natural environment. The main problem lies in Indonesia's unified legal framework under the Sustainable Agriculture Law that lacks proper mechanisms to ensure sustainable practices, focusing more on ethical agriculture rather than true sustainability which requires identification of problems and solutions. This study aims to propose a mandatory sustainability disclosure as a means to promote sustainable agriculture practices in Indonesia, thereby enhancing the implementation of SDG 2. This research is a qualitative research. The data used in this study were collected through literature review techniques, to be analyzed using descriptive qualitative data analysis techniques. The primary legal source is Law Number 22 of 2019 concerning Sustainable Agriculture. Primary data was taken to describe the reality of sustainability disclosure in Indonesia. Through normative legal research method and supported by statutory approach, findings suggest significant gaps in the current framework. This study develops a model of normative construction to revise the narrative of the existing law, and subsequently proposes a policy model based on this construction. The policy model essentially mandates agriculture establishments to provide a sustainability disclosure report, as a means of realizing SDG 2.